Additional data on species diversity of gobies (Actinopteri: Gobiiformes) in Xuan Thuy National Park, Nam Dinh province - Pham, Van Long; Chu, Hoang Nam; Dang, Thi Thanh Huong; Nguyen, Hong Hai; Tran, Duc Hau (Hue University Journal of Science: Natural Science, 2023)
Xuan Thuy National Park in the Red River Delta Biosphere Reserve is a biodiverse area that supports a variety of flora, fauna, and fishery resources. This study aims to provide new data on goby fish in this area by conducting monthly collections from 2018 to 2019. Based on morphological analysis, we identified 43 species of gobies, 27 of which were tropical fish. We added three new goby records to the fish fauna of Vietnam, three to northern Vietnam, and eight to the study site. The goby community was dominated by two species, namely Glossogobius olivaceus and Glossogobius giuris. Besides, the goby community of Xuan Thuy National Park is nearest to that of Tien Hai Wetland Nature Reserve but is far different from that of Ha Long Bay. This study area has a more diverse goby community than other locations in northern Vietnam. These findings further suggest the importance of this mangrove forest for gobies, and they are fundamental data for conservation and sustainable exploitation.